National developments in the intersection of IPR and competition law : from Maglite to Pirate Bay - Lidgard, Hans Henrik, 1946- (Swedish studies in European law ;, 2011)
This is the third volume in the series Swedish Studies in European Law, produced by the Swedish Network for European Legal Studies, a national network comprised of Swedish universities focusing on recent legal developments within European Union law. In this volume, Swedish researchers with specific interests in European Market law - intellectual property rights, competition and marketing law - have joined forces to review recent Swedish legislation and case-law of particular European interest in national Swedish Courts or the Court of Justice of the European Union ('CJEU'). The volume also inc.